A chemotherapy nano-booster unlocks wider therapeutic window for prostate cancer treatment - Rui Liao; Yuequan Wang; Ziqi Lin; Yuting Wang; Hongyuan Zhang; Qin Chen; Shenwu Zhang; Jin Sun; Zhonggui He; Cong Luo (Acta Pharmaceutica Sinica B, 2025)
Clinical chemotherapy for prostate cancer is still compromised by high treatment thresholds and severe off-target toxicity of drugs. Given the limited progress in improving therapeutic outcomes and reducing toxicity with the existing toolbox, efforts to broaden the chemotherapeutic window are highly desired. Here, we discover that gossypol (GSP, a natural compound) dramatically enhances the chemosensitivity of cabazitaxel (CTX), even at previously ineffective concentrations. Based on this interesting finding, we exploit a carrier-free chemotherapeutic nano-booster for prostate cancer treatment, which is molecularly co-assembled by GSP and cabazitaxel (CTX). GSP not only readily forms nanoassembly with CTX, but also functions as a chemotherapeutic enhancer that unlocks an ultra-low-dose chemotherapeutic window. Not only that, precise dual-drug nanoassembly confers CTX a significantly larger maximum tolerable dose. As expected, the nano-booster exerts striking therapeutic benefits in mouse prostate tumor xenograft models. This study advances chemotherapeutic window expansion and self-sensitized chemotherapy toward clinical applicability.